Design of Arduino-based Overvoltage Type time-lag Relay - Aprylianto Susilo, Rizky; Bustani, Bustani; Toyib, Toyib; Qomaruddin, Qomaruddin; Lucky Ziesya, Muhammad; Alfarizza, Rizki; Aditya Yuhendra, Effri (Universitas Muhammadiyah Surakarta, 2026)
Abstract - Voltage stability is the main prerequisite for electrical equipment to operate safely and reliably. This research design builds a single-phase protection system against overvoltage conditions. It is based on the Arduino Uno microcontroller with a time-lag relay scheme. The PZEM-004T sensor reliably monitors the input voltage of 80-260 V AC and sends the data using the UART communication protocol to the Arduino for analysis against the 192 V and 231 V thresholds. When the voltage exceeds these limits, the Arduino will automatically trigger a 5 V DC relay after a programmed time delay. This ensures that transient disturbances do not trigger premature disconnection of power. A 16x2 I2C LCD interface and three push-buttons allow users to monitor real-time voltage as well as set overvoltage, time-delay and calibration offset limits. Testing of the design results showed that the system successfully disconnected and connected the load according to the parameters, with a voltage reading error of < 1% after calibration and a trip time deviation below 10% of the set point. The research design, using easily accessible components, effectively teaches the principles of overvoltage protection relays, despite technical limitations. Keywords − overvoltage, time-lag relay, arduino, voltage protection.